Clinical management of the hypereosinophilic syndromes. Issue 3 (June 2012) - Cogan, Elie; Roufosse, Florence
Hypereosinophilic syndromes (HESs) are rare disorders characterized by marked hypereosinophilia that is directly responsible for organ damage or dysfunction. Different pathogenic mechanisms have been discovered in patient subgroups leading to the characterization of myeloproliferative and lymphocytic disease variants. In the updated terminology, idiopathic HES is now restricted to patients with HES of undetermined etiology. The practical clinical approach of patients with the different HES variants is reviewed herein, focusing on specific diagnostic tools and therapeutic options. Corticosteroids, hydroxyurea and IFN-α remain the classical agents for treatment of most patients with HESs. The specific role of therapeutic compounds that have become available more recently, namely, tyrosine kinase inhibitors and IL-5 antagonists, is discussed.